Geographic Disparities in Previously Diagnosed Health Conditions in Colorectal Cancer Patients Are Largely Explained by Age and Area Level Disadvantage - Goodwin, Belinda C.; March, Sonja; Ireland, Michael J.; Crawford-Williams, Fiona; Ng, Shu-Kay; Baade, Peter D.; Chambers, Suzanne K.; Aitken, Joanne F.; Dunn, Jeff (Frontiers in Oncology, 2018)
Background: Geographical disparity in CRC survival rates may be partly due to aging populations and disadvantage in more remote locations; factors that also impact the incidence and outcomes of other chronic health conditions. The current study investigates whether geographic disparity exists amongst previously diagnosed health conditions in CRC patients above and beyond age and area-level disadvantage and whether this disparity is linked to geographic disparity in CRC survival. Methods: Data regarding previously diagnosed health conditions were collected via computer-assisted telephone interviews with a cross-sectional sample of n=1966 Australian CRC patients between 2003 -2004. Ten-year survival outcomes were acquired in December 2014 from cancer registry data. Multivariate logistic regressions were applied to test associations between previously diagnosed health conditions and survival rates in rural, regional, and metropolitan areas. Results: Results suggest that only few geographical disparities exist in previously diagnosed health conditions for CRC patients and these were largely explained by SES and age. Living in an inner regional area was associated with cardio-vascular conditions, one or more respiratory disease, and multiple respiratory diagnoses. Higher occurrences of these conditions did not explain lower CRC-specific 10-year survival rates in inner regional Australia. Conclusion: It is unlikely that health disparities in terms of previously diagnosed conditions account for poorer CRC survival in regional and remote areas. Interventions to improve the health of regional CRC patients may need to target issues unique to socio-economic disadvantage and older age.